A Difficult Childhood: The Formative Years of the Transport and General Workers' Union. Issue 37 (September 2016) - Topham, Tony
Abstract : The Transport and General Workers' Union (TGWU), 300, 000 strong, opened its doors for business on 1 January 1922, confronted by a hostile environment. The dramatic scale and suddenness of the economic slump of 1920–22 was without precedent in British economic history. Unemployment among insured workers rose in just seven months from 2.6% in June 1920 to 17.1% in January 1922. Money wages in the whole transport industry fell by 18% between 1920 and 1923. A series of industrial defeats were inflicted on trade unions. The political climate was inimical to trade unions too. The TGWU's total union membership fell by 35% between 1920 and 1923. Its subsequent growth owed much to the union's flexible structure, designed to recognize the special interests of its participants, both in the designation of areas and in the autonomy granted to sections and groups. This facilitated more amalgamations, and provided a basis for growth in the new manufacturing industries.